2019
DOI: 10.13073/fpj-d-18-00028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Hydrothermal Treatments (Steam and Hot Compressed Water) on Physical Properties and Drying Behavior of Yellow-Poplar (Liriodendron tulipifera)

Abstract: Nonchemical high-pressure steam treatments have been intensively researched and commercialized to produce chemical-free wood products with enhanced properties. However, the utilization of high-pressure steam involves vapor-phase reactions using high-temperature steam generated at the expense of high energy input. In this research, influences of reaction media (steam and hot-compressed water) and temperature (100°C and 140°C) during thermal treatment on physical properties and drying behavior of yellow-poplar (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Salim et al [60] reported that steaming and compression at a high temperature enhanced the physical properties and dimensional stability of intensive OPT. Rahimi et al [45] reported that hydrothermal modification (140 • C) significantly changed the total porosity of yellow poplar (Liriodendron tulipifera Linnaeus) samples, and that hydrothermal modification significantly increased water absorption for all treatments except hot compressed water at 100 • C.…”
Section: Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Salim et al [60] reported that steaming and compression at a high temperature enhanced the physical properties and dimensional stability of intensive OPT. Rahimi et al [45] reported that hydrothermal modification (140 • C) significantly changed the total porosity of yellow poplar (Liriodendron tulipifera Linnaeus) samples, and that hydrothermal modification significantly increased water absorption for all treatments except hot compressed water at 100 • C.…”
Section: Physical Propertiesmentioning
confidence: 99%
“…The authors also mentioned that the MOE of the thermally modified samples was reduced with increased treatment temperature and time. Rahimi et al [45] investigated the effects of different hydrothermal modifications (steam and hot compressed water) on the physical properties and drying behavior of yellow poplar (Liriodendron tulipifera). They found that hydrothermally treated samples (100 and 140 • C) exhibited a greater modulus of elasticity than that of the control samples.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Jianxiong L. et al [6] conducted a heat treatment of poplar by steam media and established a regression model between color difference, treatment temperature, and time and obtained the conclusion that the color of wood will gradually transition from primary color to dark brown after heat treatment. Sohrab Rahimi et al [7] compared heat treatments with water and steam media, and they noted that the use of water media causes the degradation of intercellular cavities and wood cells, which can lead to an increase in wood permeability and water absorption, which, in turn, affects the moisture content of the wood, while the use of steam media changes the cell wall structure, which reduces the modulus of elasticity and modulus of rupture of wood samples.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is different from other methods because of the existence of a hydrolysis step. Nowadays, hydrothermal treatment of wood has been implemented by several researchers [7,8,10,11]. The efficacy of hydrothermal treatment is mainly dependent on treatment temperature, duration and also the heating media [12].…”
Section: Introductionmentioning
confidence: 99%